Political Budget Cycles in Public Revenues: Evidence From Fines. (November 2021) - Benito, Bernardino; Guillamón, María-Dolores; Ríos, Ana-María
This article seeks to ascertain whether local governments make improper use of their discretion and use pecuniary sanctions for electoral purposes. To this end, a sample of Spanish municipalities with a population of more than 1, 000 citizens during the period 2010 to 2016 has been used. Our results show that revenues from fines are influenced by the presence of elections. In particular, we find that local governments in an election year reduce the percentage of fines, measured either over total non-financial revenues or in per capita terms. This reduction, compared to the pre-election year, suggests that politicians use their discretionary power to issue fewer fines in election years, as they are aware that penalties are not well-regarded by citizens. In addition, we find that the most indebted municipalities, those governed by right-wing parties and the most fragmented municipalities tend to collect more revenues from fines in the pre-election year. Finally, other factors influencing revenues from fines are the number of inhabitants of the municipality, the sources of external funding that the local government has, the ideology of the rulers and their political strength.